Le care éducatif : principe actif des choix professionnels et des pratiques de travail sexués - Sophie Devineau; Aurélia Confais (Éducation et Socialisation)
The occupation of CPE and nursery schools teacher respectively account for over 70% and 90% of women in their overall numbers. A defect of parity which the sociology of gender allows to shine through the aspects of the care of prescribed working activity. Among the various findings generated by the study, there appears that men and women have different relationships to their work according to gender notably generated by the gender differentiated socialization.